Modeling of Alanya District Oba Çayı Flood Zone with MIKE Hydrological Model Program - Zübeyde Demirel; Mehmet Dikici (Doğal Afetler ve Çevre Dergisi, 2025)
Today, droughts and floods have become serious problems due to the effects of global warming. Although climate change has been an ongoing process since the beginning of the world, it is currently undergoing rapid change due to human activities. Along with climate change, many meteorological events such as heat waves, floods, and typhoons are negatively affecting life. Climate change has caused changes in rainfall patterns in many regions. It has been observed that a large portion of rainfall now occurs in the form of heavy rainfall. As a result of heavy rainfall, water flows outside riverbeds, causing floods. For this reason, determining flood-prone areas belonging to riverbeds in advance is very important in terms of reducing flood-related damage. By enhancing the capacity of river and stream beds to accommodate flood flows during floods based on pre-determined flood inundation maps, it is possible to prevent loss of life and property. Various flood modeling software programs, such as HEC-RAS and MIKE, are used to mathematically model flood events. These programs provide significant benefits in analyzing flood events and identifying risks. This study aims to assess the flood risks of the Oba Çayı River located in the Alanya district of Antalya province. Flood risk analysis was conducted and flood distributions were examined using the MIKE program with the help of discharge data with recurrence intervals obtained from the hydrograph data obtained by the 13th Regional Directorate of the State Hydraulic Works. In this context, areas with high risk potential and capable of causing floods were identified. The results of the analysis are significant for predicting and managing flood-related disaster risks prior to a flood event.